Tranexamic acid with vitamin K mixture decreases bleeding of total hip arthroplasty in a Jordanian population - Obeidat, Mohammad; Bashmaf, Omar; Alrwashdeh, Sami; Ababneh, Faris; Sharadgah, Suleiman (International Journal of Research in Orthopaedics, 2024)
Background: Bleeding of total hip arthroplasty has severe consequences on postoperative recovery. 75–90% of early bleeding after surgery and during surgery is caused by operative technical issues. tranexamic acid decreases bleeding of arthroplasty. vitamin k has late and dose sensitive effect in clotting. Methods: This retrospective investigation included subjects of middle age and of both genders scheduled for primary hip replacement at Queen Alia hospital, Jordanian Royal medical services, between March 2022 and June 2023. Subjects were classified into two groups. Group I subject were administered intravenous mixture of Tranexamic acid 10 mg/kg with vitamin K1 of 10 mg 5 min pre-skin incision followed by an infusion of Tranexamic acid 1 mg/kg/h and vitamin K1 0.2 mg/kg/h, until skin closure. Group II subjects were administered only intravenous vitamin K1 of 10 mg, 5 min pre- skin incision followed by infusion of 0.2 mg/kg/h until skin closure. Hemoglobin, packed cell volume, platelet count, prothrombin time, partial thromboplastin time and fibrinogen were tested. Bleeding and blood transfusion were remarked. Results: Group I demonstrated a remarkable less modifications in blood tests and less bleeding than group II. Group II demonstrated less bleeding after surgery. The average Hb in group I demonstrated a remarkable less reduction after surgery compared to group II. (p<0.005). No blood transfusion after surgery was needed in group I. Nine (15%) patients in group II needed one unit of blood transfusion during surgery. Conclusion: Intravenous administration of Tranexamic acid with vitamin K mixture in total hip arthroplasty decreased bleeding during and after surgery and decreased the requirement for blood transfusion.